Clinical significance of CYP2C9‐status guided valproic acid therapy in children. (13th May 2015) - Bűdi, Tamás; Tóth, Katalin; Nagy, Andrea; Szever, Zsuzsa; Kiss, Ádám; Temesvári, Manna; Háfra, Edit; Garami, Miklós; Tapodi, Adrienn; Monostory, Katalin
Summary Objectives Valproic acid (VPA)–induced adverse effects, which are sometimes serious in children, can be associated with alterations in VPA metabolism. VPA‐evoked toxicity is attributed to both the parent compound and its unsaturated metabolites, primarily formed by the cytochrome P450 (CYP)2C9 enzyme. Thus, patients' CYP2C9‐status may account for the predisposition to adverse reactions, and testing CYP2C9‐status may contribute to the improvement and rationalization of VPA therapy in children. Methods In the CYPtest group, children's CYP2C9‐status was screened before initiating antiepileptic therapy. CYP2C9‐status was estimated by the identification of defective CYP2C9 allelic variants (CYP2C9*2, CYP2C9*3) and current CYP2C9 expression in patients' leukocytes, which reflects hepatic CYP2C9 activities. When the results of CYP2C9 genotyping and CYP2C9 expression were combined, the patients' VPA‐metabolizing capacity was predicted, and VPA dosing was adjusted to the patients' CYP2C9‐status. Clinical and biochemical parameters, such as VPA serum levels, blood cell counts, liver function parameters, and adverse effects in patients of CYPtest group were compared with those of the control group treated with VPA according to conventional clinical practice. Results CYP2C9‐guided treatment significantly reduced VPA misdosing and consequently decreased the ratio of patients out of the range of target VPA blood concentrations. In the CYPtest group of children who received CYP2C9‐status adapted dose, serum alkaline phosphatase (ALP) level and the ratio of patients with abnormal ALP levels were substantially lower than in the control group. The incidence of serious side effects, notably hyperammonemia, was reduced in the CYPtest group; however, some other side effects, such as weight changes and somnolence, could not be avoided. Significance The knowledge of pediatric patients' CYP2C9‐status can contribute to the optimization of VPA dosing and to the avoidance of misdosing‐induced side effects.